Aspirations: the moral of the story. Issue 8 (17th November 2017) - Baker, William
Abstract: This article argues for the importance of studying the moral meanings that young people attach to their aspirations and plans for the future. Drawing on semi-structured interview data with 29 young people from a sixth-form college in a disadvantaged area of East London, I show that aspirations are closely connected to the formation of individual and group identities, and the making of inter-group boundaries. I argue that young people develop aspirations as part of a normatively evaluative narrative about who they are and the kind of person they hope to become. Focusing on moral meanings helps us to better understand young peoples' range of motivations for pursuing particular goals, and may help to explain why aspirations can remain high even in the absence of capitals, resources, or opportunities.